Disclosures of harming others during their most recent drinking session: Findings from a large national study of heavy‐drinking adolescents. (28th June 2021) - Lam, Tina; Laslett, Anne‐Marie; Fischer, Jane; Salom, Caroline; Ogeil, Rowan P.; Lubman, Dan I.; Aiken, Alexandra; Mattick, Richard; Gilmore, William; Allsop, Steve
Abstract: Introduction: The extant Alcohol's Harms to Others (AHTO) literature is largely comprised of reports from victims. We investigated AHTO from perpetrators' perspectives, including how harms were associated with individual characteristics, and alcohol quantities consumed during the perpetration incident. Methods: Participants ( N = 2932) were 14–19 years old, recruited primarily through social media and screened as risky drinkers. They completed face‐to‐face ( n = 594) or self‐administered ( n = 2338) surveys. They self‐reported whether during their last risky drinking session (LRDS) they had perpetrated any verbal abuse, physical abuse or property damage. A multinomial logistic regression examined whether nine factors were associated with perpetrating zero, one or 2+ categories of AHTO. Results: Eleven percent ( n = 323) reported perpetrating at least one form of AHTO (7.5% verbal, 1.9% physical and 4.6% property). Perpetration of AHTO at LRDS was uniquely associated with: younger age, male gender, experiences of childhood physical punishment, greater perpetration incident‐specific drinking, concurrent illicit drug use, and less frequent use of safety strategies while drinking in the past 12 months. Controlling for the other variables, an increase of six Australian standard drinks (60 g of alcohol) increased the odds of perpetration by 15% [95% confidence interval (CI) adjusted odds ratio (AOR) 1.08, 1.23], and an increase of 15 Australian standard drinks increased the odds by 42% (95% CI AOR 1.20, 1.69). Discussion and Conclusions: Individual characteristics, larger quantities of alcohol consumed, and a disinclination to practice harm reduction amplified risk of AHTO perpetration. This has implications for health promotion and risk prevention/reduction strategies.